Challenges and Solutions in Implementing Social Media Strategies for College Library Users in Goa - Fatte, Samir Rama; Bankapur, Vinayak (Journal of Advanced Research in Library and Information Science; Vol 11 No 4 (2024): Journal of Advanced Research in Library and Information Science, 2024)
This study explores the impact of social media strategies on collaborative learning and learner performance within college libraries in Goa. Through a survey of 98 respondents, it investigates how perceived enjoyment, ease of use, and usefulness of social media tools contribute to enhanced student engagement and academic success. Utilizing SPSS and Smart PLS for analysis, the findings reveal significant relationships between social media usage and improved collaborative learning experiences, alongside challenges such as maintaining an engaging online presence and ensuring accessibility. The research underscores the importance of tailoring social media content to meet diverse user needs and highlights the necessity for libraries to adopt user-centered approaches in their digital outreach efforts. These insights offer valuable implications for college libraries seeking to leverage social media for educational enhancement.